(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Ziziphus jujuba, commonly known as jujube or Chinese date, is valued in traditional medicine for its diverse therapeutic properties. This study investigates its importance in diabetes management, with emphasis on corosolic acid, a compound known for its antidiabetic effects. The study aims to comprehensively evaluate the antidiabetic potential of Ziziphus jujuba, specifically evaluating corosolic acid concentration, antioxidant activity, and alpha-amylase inhibition, as well as its efficacy on diabetic rat models. The study employs a combination of qualitative and quantitative analyses, in vitro assays, and in vivo experiments to assess the antidiabetic potential of Ziziphus jujuba leaf extract. Fresh leaf samples of Ziziphus jujuba were collected and subjected to corosolic acid analysis. In vitro antioxidant and antidiabetic activities were analyzed using DPPH and alpha-amylase inhibition assays, respectively. In vivo studies involved treating diabetic rat models with the leaf extract and assessing various parameters including blood glucose levels, lipid profiles, and pancreatic histopathology. The study revealed a significant concentration of corosolic acid in the leaf extract of Ziziphus jujuba, showed potent antioxidant activity and notable inhibition of alpha-amylase in in vitro assays. Treatment with the plant extract on diabetic rat models resulted in significant reductions in blood glucose levels, improvements in lipid profiles, and regeneration of pancreatic islet cells. Our study line up with previous experiments on antidiabetic effects of corosolic acid and further indicated the role of Ziziphus jujuba in diabetes management, providing a plant based substitute for glycemic control.